Sučasnì pìdhodi reformuvannâ konstitucìjnoї modelì mìscevoї publìčnoї vladi v Ukraїnì - Kalinovs′kij, Bogdan (L'vìvs'kij nacìnal'nij unìversitet ìmenì Ìvana Franka, 2013)
Analysis of modern approaches to reform of the local public authority, the need to improve the constitutional model of the administrative-territorial division, proposed changes to legislation aimed at optimizing the interaction between the executive authorities and bodies of local self-government in Ukraine.
Keywords: Ukraina; reformy samorządu terytorialnego; konstytucyjnego modelu podziału administracyjno-terytorialnego; zmiany legislacyjne